Photo‐ and Electronically Switchable Spin‐Crossover Iron(II) Metal–Organic Frameworks Based on a Tetrathiafulvalene Ligand. (12th April 2017) - Wang, Hai‐Ying; Ge, Jing‐Yuan; Hua, Carol; Jiao, Cheng‐Qi; Wu, Yue; Leong, Chanel F.; D'Alessandro, Deanna M.; Liu, Tao; Zuo, Jing‐Lin
Abstract: A major challenge is the development of multifunctional metal–organic frameworks (MOFs), wherein magnetic and electronic functionality can be controlled simultaneously. Herein, we rationally construct two 3D MOFs by introducing the redox active ligand tetra(4‐pyridyl)tetrathiafulvalene (TTF(py)4 ) and spin‐crossover Fe II centers. The materials exhibit redox activity, in addition to thermally and photo‐induced spin crossover (SCO). A crystal‐to‐crystal transformation induced by I2 doping has also been observed and the resulting intercalated structure determined. The conductivity could be significantly enhanced (up to 3 orders of magnitude) by modulating the electronic state of the framework via oxidative doping; SCO behavior was also modified and the photo‐magnetic behavior was switched off. This work provides a new strategy to tune the spin state and conductivity of framework materials through guest‐induced redox‐state switching.